CLEC12A sensitizes differentially responsive breast cancer cells to the anti-cancer effects of artemisinin by repressing autophagy and inflammation - Chatterjee, Ranodeep; Shukla, Aditya; Chakrabarti, Kausiki; Chatterji, Urmi (Frontiers in Oncology, 2023)
Background: Enhanced inflammatory responses promote tumor progression by activating toll-like receptors (TLRs), which in turn are inhibited by C-type lectin like receptors (CTLRs), like CLEC12A. Although the presence of CLEC12A in acute myeloid leukemia is well established, its role in nonhematopoietic tumors is still obscure. In hematopoietic tumors, CLEC12A mostly inhibits TLRs and modulates inflammatory responses via NF-κB signaling. In this study, the fate of tumor progression was determined by modulating CLEC12A using artemisinin (ART), a FDA-approved anti-malarial drug, known for its anti-cancer and immunomodulatory properties with minimal adverse effects on normal cells.Method: Effects of ART were primarily determined on hematological factors and primary metastatic organs, such as lungs, kidney and liver in normal and tumor-bearing BALB/c mice. Tumor-bearing mice were treated with different concentrations of ART and expressions of CLEC12A and associated downstream components were determined. CLEC12A was overexpressed in MDA-MB-231 and 4T1 cells, and the effects of ART were analyzed in the overexpressed cells. Silencing TLR4 using vivo morpholino was performed to elucidate its role in tumor progression in response to ART. Finally, CLEC12A modulation by ART was evaluated in the resident cancer stem cell (CSC) population.2 Results: ART did not alter physiology of normal mice, in contrast to tumor-bearing mice, where ART led to tumor regression. In addition, ART reduced expression of CLEC12A. Expectedly, TLR4 expression increased, but surprisingly, that of NF-κB (RelA) and JNK/pJNK decreased, along with reduced inflammation, reduced autophagy and increased apoptosis. All the above observations reverted on overexpression of CLEC12A in MDA-MB-231 and 4T1 cells. Inhibition of TLR4, however, indicated no change in the expressions of CLEC12A, NF-κB, or apoptotic markers. The effect of ART showed a similar trend in the CSC population as in cancer cells.This study, for the first time, confirmed a differential role of CLEC12A in non-hematopoietic tumor and cancer stem cells in response to ART. Subsequent interaction and modulation of CLEC12A with ART induced tumor cell death and abrogation of CSCs, confirming a more comprehensive tumor therapy with reduced risk of recurrence. Therefore, ART may be repurposed as an effective drug for cancer treatment in future.